Evaluación de la sustitución parcial de harina de pescado por harina de subproducto de camarón - Ortiz Mazamba, Dalimbert Alexander (2025)
The objective of this research was to evaluate the effect of the partial substitution of shrimp by-product meal (SBM) for fish meal (FM) on the bromatological and microbiological quality of a balanced feed. A Completely Randomized Design (CRD) was applied. The factor under study was the inclusion of different percentages of SBM: 30% (T1), 50% (T2), 60% (T3), 70% (T4), and a control (100% FM), resulting in a total of five treatments with three replicates each. Twenty percent of the balanced feed for growing chickens corresponded to fish meal, the portion in which the substitutions with SBM were made. Bromatological analyses (fiber, ash, moisture, and protein) and microbiological analyses (coliforms, molds sp., yeasts sp., and Salmonella sp.) were carried out in accordance with NTE INEN 1829 and NTE INEN 472:1988-04, respectively. The shrimp by-product meal presented bromatological characteristics with values of 21.69% ash, 12.76% fiber, 12.06% fat, 10.97% moisture, and 53.97% protein, mostly consistent with specialized literature and a microbiological quality within the permissible limits established by NTE INEN 472:1988-04. Treatment T1 (30% SBM) showed the best bromatological characteristics (protein, fiber, and moisture). The inclusion of 30% shrimp by-product meal as a partial substitute for fish meal allowed the production of a balanced feed with optimal bromatological quality and adequate microbiological safety, demonstrating its feasibility as an alternative in the formulation of balanced feeds for chickens.